EVALUATION OF THE CREDIT APPLICATION PROCESS AT PT. BPR SINAR MAS PELITA CIAWI BRANCH - Andi Usmar; Syifa Salsabila (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to examine the credit application procedure at BPR Sinar Mas Pelita Ciawi Branch, identify the challenges encountered during the process, and evaluate the solutions implemented to overcome them. The research uses a descriptive qualitative method with data collected through interviews with bank employees, direct observation during an internship program, and literature review. The findings show that the credit application procedure consists of several stages: application submission, document verification, credit analysis, credit approval, agreement signing, and fund disbursement. Common obstacles include customers’ lack of understanding of the procedure and delays in document submission. BPR Sinar Mas Pelita Ciawi Branch has implemented various strategies such as public education through social media and providing a checklist of required documents to applicants. Overall, the credit application process has been carried out effectively and efficiently.